Determining the Optimal Rice Distribution Route in Medan City Using Dijkstra's Algorithm - Jason Jason; Anita Christine Sembiring; Viviana Viviana (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Distribution is an activity carried out to spread the product throughout the market so that consumers can buy it. Distribution can also affect the price of goods. Therefore, the distribution must be effective. The purpose of this study is to determine the shortest route that is effective in distribution so that product prices are not high and the company does not suffer losses. The data analysis method used is Dijkstra's Algorithm obtained with data on the distance between the starting point and the destination point through predetermined points. The calculation results show that the shortest and fastest routes to be taken based on the dijkstra algorithm are: A-20-19-F-26-C-D-11-12-B-E with a distance of 40.71 km. There are several road routes that can be chosen to be used but the shortest route that can be taken is 40.71 km. Medan Rice Distributors are expected to choose the shortest transportation route so that rice distribution can be carried out quickly and optimally.